1999
DOI: 10.1007/s004420050949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat isolation on pollinator communities and seed set

Abstract: Destruction and fragmentation of natural habitats is the major reason for the decreasing biodiversity in the agricultural landscape. Loss of populations may negatively affect biotic interactions and ecosystem stability. Here we tested the hypothesis that habitat fragmentation affects bee populations and thereby disrupts plant-pollinator interactions. We experimentally established small "habitat islands" of two self-incompatible, annual crucifers on eight calcareous grasslands and in the intensively managed agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
373
6
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(397 citation statements)
references
References 41 publications
13
373
6
5
Order By: Relevance
“…This loss of floral diversity has been linked to the increased use of inorganic fertilisers, reseeding, improved drainage and a greater frequency of cutting and grazing (Blackstock, et al, 1999;Bullock, et al, 2011). For those areas that have escaped the impact of modern practices and remain under traditional extensive management systems, the diversity and cover of flowering plants represents a key resource for many insect pollinators (Forup and Memmott, 2005;Noordijk, et al, 2009;Steffan-Dewenter and Tscharntke, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This loss of floral diversity has been linked to the increased use of inorganic fertilisers, reseeding, improved drainage and a greater frequency of cutting and grazing (Blackstock, et al, 1999;Bullock, et al, 2011). For those areas that have escaped the impact of modern practices and remain under traditional extensive management systems, the diversity and cover of flowering plants represents a key resource for many insect pollinators (Forup and Memmott, 2005;Noordijk, et al, 2009;Steffan-Dewenter and Tscharntke, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…those containing both grassland and arable) the retention of such areas can play a key role in the maintenance of insect pollinators, particularly for taxa such as bees that forage at a landscape scale (Decourtye, et al, 2010 ;Steffan-Dewenter and Tscharntke, 1999). As insect pollinators are estimated to support 9.5% of the worldwide production of key vegetables, fruits and oil producing crops (worth €153 billion), this loss of species-rich grasslands may have economic consequences for the provision of this ecosystem service (Gallai, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on experimentally fragmented plant populations has demonstrated that this process does indeed pose a plausible threat (Ste¡an-Dewenter & Tscharntke 1999). To establish this link between declining pollination and declining reproduction, evidence is required that the reproductive output of plants growing in fragments is pollen limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have showed that there is a timing correlation between the pollen collection by honeybees and the flowering period (Andrada and Telleria, 2005;Dimou and Thrasyvoulou, 2007). Moreover, honeybees collect food only from a restricted area around the hive (Visscher and Seeley, 1982;Ekert, 1993;Steffan-Dewenter and Tscharntke, 1999). Thus, compared to the air pollen traps, the pollen collected by traps adjusted to beehives strictly represents the taxa only from the area around the apiary.…”
Section: Discussionmentioning
confidence: 99%